Nitrogen fertilization after robusta coffee pruning in Cambisols - Díaz, Alberto Pérez; González, Carlos Alberto Bustamante; Alonso, Gloria Marta Martín; Espinosa, Ramón Antonio Rivera; Núñez, Rolando Viñals; Castro, Maritza Idilia Rodríguez (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the influence of nitrogen mineral fertilization, after robusta coffee pruning, on crop yield and some chemical (pH, organic matter) and microbiological (biological gas exchange and nitrification) soil indicators in two Cambisols in Tercer Frente, Santiago de Cuba, and La Alcarraza, Holguín, during the years 2003–2007. The response to increasing doses of N (0 up to 400 kg ha-1), in the presence of fixed amounts of P (50 kg ha-1) and K (160 kg ha-1), was studied in a randomized block design with four replicates. To obtain coffee yields between 0.50 and 0.84 Mg ha-1, 75 kg ha-1 N are sufficient. In both soils, applications of 100 kg ha-1 N allowed for coffee yields between 1.22 and 1.25 Mg ha-1. With a dose of 153 kg ha-1 N, 1.80 Mg ha-1 coffee yields are obtained, whereas for yields higher than 2 Mg ha-1, it is necessary to apply 200 kg ha-1 N. There was a significant coffee yield increment per each kilogram of N applied, which ranged from 2.13 to 7.80. The proposed doses per site did not affect the microbial activity or soil organic matter. There was a soil pH reduction compared to its initial stage.